Synthesis of research on sweet potato (Ipomoea batatas) with a view to its valorization - ZANNOU, Aimé; GBAGUIDI, ACAKPO NONVIGNON MAGLOIRE; AHOUSSI-DAHOUENON, Edwige (My University, 2017)
Sweet potato (Ipomoea batatas) is one of the major food-producing tubers for human consumption belonging to the convolvulaceae family. Sweet potato provides strategic opportunities to improve nutrition and rural incomes in several countries and regions affected by micronutrient deficiencies. It is grown in most parts of Africa and is well established as a food security crop in many densely populated countries. It is an important source of carbohydrates (96%), in the form of simple carbohydrates and dietary fibers, which play an important role in energy deficiencies. Sweet potato is a good source of vitamins A compared to other roots and tubers. Its vitamin C content is also remarkable. It contains vitamins E, B1, B2 and folic acid. It is rich in minerals essential to the functioning of the body such as zinc and calcium
Keywords: sweet potato; tuber; micronutrients; food security